Attitude and Opinion of Neurosurgeons Concerning Protective Bicycle-Helmet Use - Jung, Carla Sabine; Zweckberger, Klaus; Schick, Uta; Unterberg, Andreas (Journal of neurotrauma, 2010)
Wearing protective helmets decreases the risk of incurring traumatic brain injury (TBI) in bicycle accidents. In 2007, the German Neurosurgical Society advocated compulsory use of bicycle helmets. Although neurosurgeons are the specialists who primarily treat patients with TBI in Europe, the distribution of helmet users among neurosurgeons (NS), as well as factors that influence the decision to wear helmets and whether professional knowledge or experience in TBI influences the use or attitude concerning bicycle helmets, remains unclear. A total of 55 neurosurgical departments in Germany, Austria, and Switzerland were contacted and asked to answer anonymous questionnaires concerning helmet use and TBI experience. To compare the neurosurgical attitude with that of a “non-neurosurgical, non-TBI-educated” control group, people of the general public (PUB) were interviewed. A total of 465 NS and 546 PUB returned questionnaires, with 49.7% of the NS and 44.5% of PUB indicated that they wear helmets while bicycling. Trauma experience did effect the personal decision of whether to wear bicycle helmets. Support of compulsory use was influenced by TBI experience. Furthermore, the incidence of helmet use in children was correlated to actual helmet use and disposition of their parents to make helmet use compulsory. NS and PUB behaved in similar ways. Only half wear protective helmets, while the others show cognitive dissonant behavior. With respect to compulsory helmet use, NS are also split in half. Experience with TBI and trauma education has effects. However, education alone does not suffice in promoting the use of bicycle helmets.
Gesehen am 09.10.2023